Jawabanmu

Jawaban paling cerdas!
2014-06-14T14:58:47+07:00
Misal akar - akar persamaaan dari 2x² - (p+1)x +1 adalah a dan b, maka
a + b = - (-(p+1))/2
a + b = (p+1)/2
.
ab = 1/2
.
(a + b)² = a² + b² + 2ab
(a + b)² = 3 + 1
(a + b)² = 4
a + b = 2 atau -a
untuk a + b = 2
(p+1)/2 = 2
p + 1 = 4
p = 3
untuk a + b = -2
(p+1)/2 = -2
p + 1 = -4
p = -5
karena p bernilai positif maka p = 3
1 5 1
2014-06-14T15:26:24+07:00
X1^2+x2^2 = (x1+x2)^2-2.x1.x2
3= ((p+1)/2)^2-2(1/2)
p^2+2p-15=0
 (p-3) (p+5)

p1=3 ---->bernilai positif